Mitro-aortic aneurysms in children: single-centre experience and review of the literature. (26th September 2013) - Magalhães, Manuel; Bakero, Luis; Fragata, José; Paramés, Filipa; Freitas, Isabel; Rebelo, Mónica; Martins, José D.; Trigo, Conceição; Pinto, Fátima F.
Abstract Objectives: This publication aims to report the cases of four children with pseudoaneurysm of the mitral-aortic intervalvular fibrosa and carry out a review of the literature. Background: Pseudoaneurysm of the mitral-aortic intervalvular fibrosa is a very rare anomaly in children. It can be either congenital or acquired, namely, after bacterial endocarditis or cardiac trauma. This pathology does not usually cause specific symptoms but its outcome may be potentially fatal. Methods: We report the cases of four patients presenting with pseudoaneurysm of the mitral-aortic intervalvular fibrosa, referred for treatment in a paediatric cardiology clinic. Patient clinical notes were retrospectively reviewed for aetiology, clinical presentation, diagnostic work-up, surgical treatment, and follow-up. Literature on the subject was extensively reviewed. Results: In three patients, pseudoaneurysm of the mitral-aortic intervalvular fibrosa was acquired, being secondary to bacterial endocarditis in two cases and establishing after mitral surgery in another case. The remaining patient had a "congenital" aetiology – no other cause could be traced. The diagnosis was achieved by transthoracic echocardiography for all patients, and confirmed in all by trans-oesophageal echocardiography, to better define morphological details and to access flow into the aneurysmal formation. All patients were submitted to corrective cardiac surgery. Of the patients, three survived and were cured by surgery, staying asymptomatic, and one died after repeated interventions, for persistent endocarditis. Conclusions: Pseudoaneurysm of the mitral-aortic intervalvular fibrosa is a rare but potentially fatal anomaly. In our experience, surgical cure was achieved for the majority of the cases, except for a case for which infection could not be locally eradicated, leading to multiple reinterventions.